Patients value their own pain over braking safety when deciding when to return to driving: a discrete choice experiment on lower extremity injuries. Issue 3 (7th September 2022) - DeLeon, Genaro A.; Rolle, Nicholas P.; Burke, Cynthia E.; McKegg, Phillip C.; Hannan, Zachary D.; Ghulam, Qasim M.; Gupta, Jayesh; Bangura, Abdulai; O'Connor, Katherine C.; Slobogean, Gerard P.; O'Toole, Robert V.; O'Hara, Nathan N.
Abstract: Objective: To quantify patient preferences towards time to return to driving relative to compromised reaction time and potential complication risks. Design: Cross-sectional discrete choice experiment. Setting: Academic trauma center. Patients: Ninety-six adult patients with an operative lower extremity fracture from December 2019 through December 2020. Intervention: None. Main Outcome Measurement: Patient completed a discrete choice experiment survey consisting of 12 hypothetical return to driving scenarios with varied attributes: time to return to driving (range: 1 to 6 months), risk of implant failure (range: 1% to 12%), pain upon driving return (range: none to severe), and driving safety measured by braking distance (range: 0 to 40 feet at 60 mph). The relative importance of each attribute is reported on a scale of 0% to 100%. Results: Patients most valued a reduced pain level when resuming driving (62%), followed by the risk of implant failure (17%), time to return to driving (13%), and braking safety (8%). Patients were indifferent to returning to driving at 1 month (median utility: 28, interquartile range [IQR] −31 to 80) or 2 months (median utility: 59, IQR: 41 to 91) postinjury. Conclusion: Patients with lower extremity injuries demonstrated a willingness to forego earlier return to driving if it might mean a decrease in their pain level. Patients are least concerned about their driving safety, instead placing higher value on their own pain level and chance of implant failure. The findings of this study are the first to rigorously quantify patient preferences toward a return to driving and heterogeneity in patient preferences. Level of Evidence: V